1998
DOI: 10.1159/000017051
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Plaques: Stages in Life History or Independent Origin?

Abstract: Several types of discrete β-amyloid (Aβ) deposit or senile plaque have been identified in the brains of individuals with Alzheimer’s disease and Down’s syndrome. The majority of these plaques can be classified into four morphological types: diffuse, primitive, classic and compact. Two hypotheses have been proposed to account for these plaques. Firstly, that the diffuse, primitive, classic and compact plaques develop in sequence and represent stages in the life history of a single plaque type. Secondly, that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 104 publications
(206 reference statements)
5
71
0
3
Order By: Relevance
“…The concurrent existence of various Aβ structures in the retina of the same patient may suggest that Aβ accumulates in different disease stages. This supports the hypothesis that different types of Aβ deposits develop independently rather than sequentially from the same plaque type (90). It is likely that multiple factors contribute to the formation of each type of retinal deposit, but the underlying mechanisms of plaque and nonfibrillar oligomer formation in the retina are not yet understood.…”
Section: Discussionsupporting
confidence: 77%
“…The concurrent existence of various Aβ structures in the retina of the same patient may suggest that Aβ accumulates in different disease stages. This supports the hypothesis that different types of Aβ deposits develop independently rather than sequentially from the same plaque type (90). It is likely that multiple factors contribute to the formation of each type of retinal deposit, but the underlying mechanisms of plaque and nonfibrillar oligomer formation in the retina are not yet understood.…”
Section: Discussionsupporting
confidence: 77%
“…Diffusely distributed extracellular Aβ then assembles into toxic oligomers, aggregates and eventually condenses into senile plaques over a long period of time (Armstrong, 1998;Marchesi, 2005;Torp et al, 2000). However, emerging evidence has demonstrated that a large fraction of Aβ is generated in intracellular compartments rather than at cell surfaces (Gouras et al, 2005;LaFerla et al, 2007).…”
Section: Amyloid Deposition and Autophagy-lysosomal Machinerymentioning
confidence: 99%
“…Three morphological subtypes of Aβ deposit are commonly observed in AD: 1) diffuse ('pre-amyloid') deposits, in which the Aβ is not in a fibrillar form with a β-pleated conformation, dystrophic neurites (DN) and paired helical filaments (PHF) being largely absent, 2) primitive ('neuritic') deposits, in which the Aβ is in a fibrillar form and is associated with DN and PHF, and 3) classic ('dense-cored') deposits, in which Aβ is highly aggregated to form a central amyloid plaque 'core' surrounded by a 'ring' of DN [3,8,[10][11][12]20]. In the cerebral cortex in AD, Aβ deposits [2] and NFT [54] often exhibit significant variation in density across the cortex from pia mater to white matter, maximum density occurring within different layers [2,54].…”
Section: Introductionmentioning
confidence: 99%